PENGARUH KOMPENSASI, MOTIVASI KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERSONEL POLRI BIDDOKKES POLDA KALIMANTAN SELATAN - Menik Sri Rahayu; Achmad Firdiansjah; Harianto Respati (Jurnal Ilmiah Ekonomi Bisnis, 2019)
The purpose of the study was to analyze the effect of leadership motivation and job Polri Biddokkes Polda Kalsel always effort to improve work performance. It is influenced by compensation, motivation, and organizational commitment. To analyzing and to know the influence, the research need to do  in Polri Biddokkes Polda Kalsel. Quantitative method is used in this research. The population is all members of  Polri Biddokkes Polda Kalsel. They are 63 persons. Technique of sampling is census. This research samples are 63 person. The datas collection technique is questioner. Data is analyzed by linier regression analysis.The research result shows that compensation, motivation, and organizational commitment have influence significantly to the performance partially and simultance. Polri Biddokkes Polda Kalsel need to improve compensation, motivation, and organizational commitment to improve because these variables have influence significantly to the performanceKey Words: Performance, compensation, motivation, and organizational commitment